Review of the Umthombo Youth Development Foundation scholarship scheme, 1999-2013 - Andrew Ross; Gavin MacGregor; Laura Campbell (AOSIS, 2015)
Introduction: Staffing of rural and remote facilities is a challenge throughout the world. Umthombo Youth Development Foundation (UYDF) has been running a rurally based scholarship scheme since 1999.The aim of this review is to present data on the number of students selected, their progress, graduation and work placement from inception of the scheme until 2013. Methods: Data were extracted from the UYDF data base using a data collection template to ensure all important information was captured. Results: Since 1999, 430 rural students across 15 health disciplines have been supported by UYDF. The annual pass rate has been greater than 89%, and less than 10% of students have been excluded from university. All graduates have spent time working in rural areas (excluding the 32 currently doing internships) and 72% (52/73) of those with no work-back obligation continue to work in rural areas. Discussion and conclusion: The UYDF model is built around local selection, compulsory academic and peer mentoring and social support, comprehensive financial support and experiential holiday work. The results are encouraging and highlight the fact that rural students can succeed at university and will come back and work in rural areas. With 46% of the South African population situated rurally, greater thought and effort must be put into the recruitment and training of rural scholars as a possible solution to the staffing of rural healthcare facilities. The UYDF provides a model which could be replicated in other parts of South Africa.